Hope and well-being in the elderly - Pessoa, Patrícia (2014)
Introduction The concepts of well-being and hope are associated with life satisfaction. Public policies should include the promotion of quality of life in the elderly. Objectives The current study sought out to address the concepts of hope and well-being in the elderly, analysing the role of socio-demographic variables. It also aimed to characterize this population in terms of other quality of life indicators such as perception of general health status, loneliness and degree of activity. Method The sample included 130 elderly people, both from the community and institutionalized, with ages between 65 and 94 years old. Participants answered questions about socio-demographic data, quality of life indicators, cognitive functioning and measures of hope (HP; Snyder et al.; 1991), life satisfaction (SWLS; Diener et al, 1985), and positive and negative affect (PANAS; Watson, Clark, & Tellegen, 1998). Results The majority of participants perceived their health status as reasonable and mentioned feelings of loneliness. Only 20% considered themselves active. Men presented higher levels of hope when compared with women. Participants who were not institutionalized showed higher levels of hope and positive affect, considering themselves more active when compared to the ones living in nursing homes or attending day centres. Hope showed to be positively correlated with life satisfaction, positive affect, health status perception and degree of activity, and negatively correlated with negative affect. Negative affect showed to be correlated with the perception of loneliness. Conclusion This study enhances the importance of socio-demographic and psychological variables in the promotion of well-being in the elderly.